Freeman–Sheldon syndrome: a case report - L. A. CORRIGAN, C. A. DUNCAN & T. A. GREGG (Paediatric Dentistry, 2006)
Freeman-Sheldon Syndrome is a rare craniofacial syndrome that has not been described in the dental literature to date. The main feature of relevance is severe microstomia, which limits access for routine dental care.